Toward a new focus in antibiotic and drug discovery from the Streptomyces arsenal - Antoraz, Sergio; Santamaría, Ramón I.; Díaz, Margarita; Sanz, David; Rodríguez, Héctor (Frontiers in Microbiology, 2015)
Emergence of antibiotic resistant pathogens is changing the way scientists look for new antibiotic compounds. This race against the increased prevalence of multi-resistant strains makes it necessary to expedite the search for new compounds with antibiotic activity and to increase the production of the known. Here, we review a variety of new scientific approaches aiming to enhance antibiotic production in Streptomyces. These include: i) elucidation of the signals that trigger the antibiotic biosynthetic pathways to improve culture media, ii) bacterial hormone studies aiming to reproduce intra and interspecific communications resulting in antibiotic burst iii) co-cultures to mimic competition-collaboration scenarios in nature, and, iv) the very recent in situ search for antibiotics that might be applied in Streptomyces natural habitats. These new research strategies combined with new analytical and molecular techniques should accelerate the discovery process when the urgency for new compounds is higher than ever.